Moral credit and its role in shaping social and economic processes - Roman Maria Lusawa (Rozprawy Społeczne)
Abstract The article presents the concept of moral credit one of the key notions of the concept of energy-based economics which was introduced by Stanisław Pszczółkowski, an outstanding economist from the era of the Second Polish Republic.